Optimization of biosorption of Zn(II) ions from aqueous solutions with low-cost biomass Trametes versicolor and the evaluation of kinetic and thermodynamic parameters. Issue 26 (2nd June 2016) - Şahan, Tekin; Ceylan, Hasan; Aktaş, Nahit
Abstract: The optimum biosorption conditions for removing Zn(II) ions from aqueous solutions by naturally powdered Trametes versicolor were successfully evaluated through a multi-step response surface methodology. The conducted experiments were based on a central composite design. The most influential factors on the biosorption process were initial pH (5–6.7), temperature (18–30°C), and initial Zn(II) concentration (30–70 mg L −1 ). Based on the statistical analysis, the optimum conditions for Zn(II) biosorption were found to be 5.74, 24.57°C, and 60.95 mg L −1 for initial pH, temperature and Zn(II) concentration, respectively. Under these optimum conditions, the maximum amount of biosorbed Zn(II) ions was 43.87 mg Zn(II) per g dry cells. The proposed quadratic model fits very well to the experimental data. Furthermore, a Dubinin–Radushkevich isotherm model described the biosorption of Zn(II) ions on the biosorbent better than the common isotherm models, while kinetic studies showed that Zn(II) biosorption matched pseudo-second-order kinetics. Moreover, thermodynamic parameters, such as the changes in free energy, enthalpy, and entropy, were also calculated for the biosorption of Zn(II) ions onto T. versicolor . It was concluded that naturally powdered T. versicolor is a suitable biosorbent for the removal of Zn(II) ions from aqueous solutions.